Implementing Outcome-Based Education in Higher Education Programs: A Multiple Case Study in Vietnam and Laos (Journal of Contemporary Educational Policies and Practices, 2024)
Outcome-based education (OBE) has been an effective framework for teaching, learning and assessment of many higher education institutions worldwide for the past few decades. This study aims to investigate the OBE implementation in four universities across Vietnam and Laos. A multiple case study with personal reflection and document analysis was employed to identify the achievements and obstacles. The research results show that the OBE implementation changed lesson plans and classroom activities, and enhanced student engagement within the teaching and learning processes. However, teachers and students encountered challenges when they implemented OBE in their lessons. The paper concludes that despite the difficulties in implementation, the student-centered approach of OBE exerted a positive influence on student learning in the investigated institutions.
Keywords: Quality improvement; outcome-based education (OBE); student-centered learning; learning outcomes; constructive alignment; Southeast Asia